2019
DOI: 10.2147/idr.s219117
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacodynamics Of Linezolid-Plus-Fosfomycin Against Vancomycin-Susceptible And -Resistant Enterococci In Vitro And In Vivo Of A <em>Galleria mellonella</em> Larval Infection Model</p>

Abstract: ObjectivesTo explore the in vitro and in vivo antibacterial activity of linezolid/fosfomycin combination against vancomycin-susceptible and -resistant enterococci (VSE and VRE), and provide a theoretical basis for the treatment of VRE.MethodsThe checkerboard method and time-kill curve study were used to evaluate the efficacy of linezolid combined with fosfomycin against VSE and VRE. The transmission electron microscopy (TEM) was employed to observe the cell morphology of bacteria treated with each drug alone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In this study, the FICI values of 43 strains indicated that linezolid-fosfomycin combination showed synergistic or additive effect on 69.8% of the tested strains and no antagonistic effects was observed. Consistent with this experiment, the synergistic antibacterial activity of the linezolid-fosfomycin combination against Staphylococcus aureus and Enterococcus was also confirmed in vitro time-killing curve ( Chai et al, 2016 ; Chen et al, 2018 ; Qi et al, 2019 ). However, research on the combination to prevent resistance was still lacking.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, the FICI values of 43 strains indicated that linezolid-fosfomycin combination showed synergistic or additive effect on 69.8% of the tested strains and no antagonistic effects was observed. Consistent with this experiment, the synergistic antibacterial activity of the linezolid-fosfomycin combination against Staphylococcus aureus and Enterococcus was also confirmed in vitro time-killing curve ( Chai et al, 2016 ; Chen et al, 2018 ; Qi et al, 2019 ). However, research on the combination to prevent resistance was still lacking.…”
Section: Discussionsupporting
confidence: 80%
“…Fosfomycin, due to its unique mechanism of action, has a synergistic effect with a variety of antibiotics and is not easy to produce cross-resistance ( Falagas et al, 2016 ). The previous study of our group confirmed that linezolid combined with fosfomycin has an in vitro synergistic effect on Enterococcus and Staphylococcus aureus ( Chen et al, 2018 ; Qi et al, 2019 ). However, the ability of the combination to prevent enterococcus resistance remains to be studied.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Combinations of vancomycin with oritavancin have also been tested but have not shown better results than individual treatments with the antibiotics [ 66 ]. The combination of linezolid with fosfomycin is promising, as it has been shown that synergy is possible between these two molecules in the G. mellonella larvae model [ 67 ]. The authors supposed that fosfomycin, by acting on cell wall synthesis via MurA inhibition, promotes linezolid penetration, showing increased activity on both VRE [ 67 ] and MRSA ( Figure 1 ) [ 68 , 69 ].…”
Section: Alternatives To Vancomycinmentioning
confidence: 99%
“…The combination of linezolid with fosfomycin is promising, as it has been shown that synergy is possible between these two molecules in the G. mellonella larvae model [ 67 ]. The authors supposed that fosfomycin, by acting on cell wall synthesis via MurA inhibition, promotes linezolid penetration, showing increased activity on both VRE [ 67 ] and MRSA ( Figure 1 ) [ 68 , 69 ]. In addition, an activity on biofilms of vancomycin resistant E. faecium has been demonstrated with this combination [ 69 ].…”
Section: Alternatives To Vancomycinmentioning
confidence: 99%